Integrating Computer Vision and Probabilistic Machine Learning for Enhanced Predictive Maintenance in Manufacturing Systems - Sandeep Singh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
As the industry transitions to Industry 4.0, the use of predictive maintenance (PdM) in factories has become crucial for achieving high efficiency and lower costs. Despite these powerful models, the use of deep learning in PdM is hindered by concerns about their reliability, interpretability, and the uncertainty they introduce. This paper outlines a combination of computer vision and probabilistic machine learning that helps improve decision-making in predictive maintenance. Using a conversion process, time-series information from sensors is transformed into images, allowing Convolutional Neural Networks (CNNs) to understand the spatial details of the machine’s health. The challenge of model confidence is overcome by using Monte Carlo (MC) Dropout during inference in the CNN to generate multiple possible outcomes. The integration enables immediate uncertainty estimation, which plays a crucial role in critical maintenance decisions. The system proposed in this study is evaluated against two well-known interpretable models using classification metrics, ROC curves, and calibration plots. This model indicated that CNN+MC Dropout performs better with visual scenes and uncertainty detection, but traditional models are better at classifying and guiding predictions. As a result, both understanding and trusting a model, along with obtaining accurate results, are crucial. The research demonstrates that uncertainty-aware deep learning enhances our experience and trust in the system. Further studies will include work on live camera images using temporal models based on recurrent probabilistic networks.